Iron pill pneumonitis with reactive lymph nodes. Issue 4 (2nd October 2018) - Tlhabano, Letlhogonolo; Mankikar, Rohan; Odigwe, Chibuzo; Owens, William; Grant, Lawrence; Arya, Rohan
Abstract: Iron pill pneumonitis can result from accidental aspiration. It usually presents as a triad of airway inflammation, aspiration, and hemosiderin deposition. We report a case of an elderly woman with chronic cough, infiltrates, and lymphadenopathy on imaging alongside nonnecrotizing granulomas on biopsy diagnosed with iron pill pneumonitis.